Management of Stemphylium Blight of Lentil by the Application of Different Dose of Chemical and Biological Fungicides - Aryal, Laxman; Baidya, Suraj; Bastola, Bishwash Raj; Poudel, Padam Prasad (Journal of the Institute of Agriculture and Animal Science, 2023)
Field experiment was conducted at Plant Pathology block of Grain Legumes Research Program, Khajura, Banke during 2018 to evaluate the different doses of chemical and biological fungicides against Stemphylium blight disease of Lentil. The experimental design was laid in Randomized Complete Block design in field condition with three replications. Altogether 3 fungicides, 2 chemical {Saff (Carbendazim 12%+ Mancozeb 63%); Farm guard (Chlorothalonil 75% WP} at the dose of 1.5 gm, 2 gm and 2.5 gm per liter water and one biological {Commericial Phytoderma (Trichoderma harzianum) at the dose of 2.5 gm, 3 gm and 3.5 gm per liter water along with no fungicide application (control) was evaluated. Lowest mean disease severity (28.89) was obtained when Farm guard (Chlorothalonil @ 2.5 gm/ water) was applied followed by Saff (30) at the same dose. Highest mean disease severity (43.33) was obtained when no fungicide was applied. Similarly lowest Area Under Disease Progress Curve (AUDPC) (204.2) was obtained when Saff @ 2.5 gm/lit water was applied followed by Chlorothalonil (210) at the same dose. Highest AUDPC (291.7) was obtained in control plot. In case of grain yield Chlorothalonil @2gm per liter water obtained highest yield (836 kg/ha) with highest yield increase percent (34.6%). Lowest grain yield was obtained from control plot (546 kg/ha) followed by Trichoderma (624 kg/ha) when sprayed at 2.5 gm per liter water. Thus, from the study it is concluded that Chlorothalonil @ 2 gm when applied timely for three times can manage the Stemphylium blight disease.